Gymnasielärares uppfattningar av kvalitet i gymnasiearbetet - Maria Calissendorff; Ylva Ståhle (Dalarna university, 2021)
With the latest upper-secondary school regulations, all students must complete a diploma project. The diploma project in the university preparatory programs has been given a more prominent role than the previous project work and should be seen as a preparation for higher studies. The article presents results from a sub-study within a major collaborative project on the diploma project. The purpose of the sub-study was to increase the knowledge of what is perceived as quality in the diploma project school work within the framework of the social science program through focus group discussions with secondary school teachers. Based on a phenomenographic analysis, four qualitatively different categories were identified: academic quality is perceived as that structure is followed, knowledge is obtained, language is mastered and that research awareness is shown. The results showed that the upper secondary school teachers' perceptions were primarily dominated by a skills discourse.